UTHM Entrepreneur Service Management System - Khairul Hakimi Azwad; Zainal, Nurezayana (Applied Information Technology And Computer Science, 2023)
The UTHM Entrepreneur Service Management System is a management system for and could be user by the customer, seller and administrator at Universiti Tun Hussein Onn Malaysia (UTHM). The aim of developing this system is to solve the problems due to the absence of a proper system and to ease the process of entrepreneurial activity in UTHM. The system being developed using the Software Development Life Cycle (SDLC) model to ensure a smooth flow of work and organize. The system provide a central platform for advertisements, making it easier for sellers to promote their products and services, and for customers to access and purchase those product and service. At the same time, the administrator could monitor the entrepreneurial activities that been done and extract information from the system. By having this system, it will provide a safe and reliable marketplace, reducing the risk of fraud and scams, and making it easier for sellers to conduct their business. The development of this system able to make the process of entrepreneurship simpler and more efficient for users, helping users to improve their management process and achieve their goals.